(untitled) - Allen, Monroe (Australia, 2004)
Dictionary helps beginning and intermediate students build their vocabulary and make the transition from bilingual and picture dictionaries to more comprehensive dictionaries.
Keywords: English language,English language,Dictionaries; Dictionaries,Textbooks for foreign speakers; United States,Americanisms